Ownership or Performance: What Determines Board of Directors' Turnover in Italy? - Giorgio Brunello; Clara Graziano; Bruno Maria Parigi (Institute for the Study of Labor (IZA), 2000)
This paper studies the turnover of board of directors members in a sample of 72 companies listed on the Milan Stock Exchange during the period 1988-1996. We investigate whether board members change more frequently when company performance is poor, as the literature suggests, and whether and how the ownership structure of Italian companies affects these relationships. We find that there is a statistically significant and negative relationship between firm performance and CEO turnover and that this relationship depends on the ownership structure of firms. Turnover is lower in family controlled firms and higher in firms that experienced a change in the controlling shareholder. The latter firms also have a stronger turnover-performance relationship. We find evidence supporting the hypothesis that changes in control are an extreme form of turnover. We also find evidence of a monitoring role of the second largest shareholder. Also the turnover of top executives exhibits a negative relationship with performance. Board turnover instead is unrelated to performance but is related to the firm?s ownership structure. Overall our findings suggest that the characteristics of the Italian economy deeply affect the turnover of directors and have implications that go beyond the specific case study.
Keywords: J63; G34; 330; Board of directors; corporate governance; financial agency; Arbeitsmobilität; Vorstand; Eigentümerstruktur; Corporate Governance; Unternehmensentwicklung; Italien